1995
DOI: 10.1083/jcb.129.3.831
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-dependent translocation of phosphoinositide 3-kinase to the cytoskeleton of thrombin-activated platelets involves specific interactions of p85 alpha with actin filaments and focal adhesion kinase.

Abstract: Abstract. Thrombin-induced accumulation of phosphatidylinositol 3,4-bisphosphate (Ptdlns(3,4)P2) but not of PtdIns(3,4,5,)P3 is strongly correlated with the relocation to the cytoskeleton of 29 % of the p85o~ regulatory subunit of phosphoinositide 3-kinase (Ptdlns 3-kinase) and is accompanied by a significant increase in Ptdlns 3-kinase activity in this subcellular fraction. Actually, Ptdlns(3,4)P2 accumulation and Ptdlns 3-kinase, pp60 ~-s'~, and p125 eA~ translocations as well as aggregation were concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
135
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(140 citation statements)
references
References 52 publications
4
135
1
Order By: Relevance
“…Expression of NEP in these cells is also associated with a loss of the interaction of p85 with FAK. Numerous studies have suggested that FAK associates with PI3-K (23,26,32) and this association affects the integrity of the actin cytoskeleton (32) and cell migration (26), although it remains controversial whether PI3-K-mediated cell migration is dependent on FAK (26,33). Thus, we hypothesize that in PC cells NEP's effect on cell migration and FAK phosphorylation is also mediated by inhibition of FAK-PI3-K interaction.…”
Section: Discussionmentioning
confidence: 97%
“…Expression of NEP in these cells is also associated with a loss of the interaction of p85 with FAK. Numerous studies have suggested that FAK associates with PI3-K (23,26,32) and this association affects the integrity of the actin cytoskeleton (32) and cell migration (26), although it remains controversial whether PI3-K-mediated cell migration is dependent on FAK (26,33). Thus, we hypothesize that in PC cells NEP's effect on cell migration and FAK phosphorylation is also mediated by inhibition of FAK-PI3-K interaction.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to its p110 binding site, the p85 subunit contains SH2 and SH3 domains which mediate its interactions with other cellular proteins. Association of FAK with PI 3-kinase in response to integrin activation has been demonstrated in both platelets (66) and fibroblasts (67). In addition, FAK/PI 3-kinase association in fibroblasts is stimulated by cell treatment with plateletderived growth factor (PDGF) (68), suggesting a mechanism of cross-talk between integrin and growth factor signaling pathways.…”
Section: Pi 3-kinasementioning
confidence: 99%
“…These phosphorylation events can activate Pyk2 by enabling subsequent tyrosine phosphorylations (particularly at Tyr402) via mechanisms that are incompletely understood (Della Rocca et al 1997;Soltoff 1998;Zwick et al 1999;Heidinger et al 2002;Fan et al 2005;Montiel et al 2007). It has also been well established that Fak and Pyk2, when activated by tyrosine phosphorylation, are each able to activate PI3K: tyrosine-phosphorylated Fak binds p85, the PI3K regulatory subunit, via both the SH3 and SH2 domains (Chen and Guan 1994;Guinebault et al 1995;Chen et al 1996). In addition, both tyrosine-phosphorylated Fak and Pyk2 are capable of activating Ras via the conserved Grb2-SoS pathway (Schlaepfer et al 1994;Dikic et al 1996;Avraham et al 2000;Rocic et al 2001), which could in principle lead to the Ras-dependent, p85-independent activation of PI3K.…”
Section: Discussionmentioning
confidence: 99%
“…CaMKII also phosphorylates mammalian Fak on C-terminal serine residues, although the functional significance of these phosphorylation events remains unknown (Fan et al 2005). Furthermore, both Pyk2 and Fak are capable of activating PI3K (Chen and Guan 1994;Schlaepfer et al 1994;Guinebault et al 1995;Chen et al 1996;Dikic et al 1996;Avraham et al 2000;Rocic et al 2001;Montiel et al 2007). Two CaMKII phosphorylation sites on Fak, serines 843 and 910, are conserved in DFak, raising the possibility that CaMKII phosphorylates DFak at these serine positions, which leads to DFak and then PI3K activation (Grabbe et al 2004).…”
Section: Camkii Regulates Pi3k Activity In Drosophila Motor Nerve Termentioning
confidence: 99%